Impact of Colonialism on Urban Development in Indonesia: A Case Study of Medan - Fivie Safitri; Agrifa Ido Arta Manalu; Indah Chofifah Suge Muliani; Diraningsih Zai; Rosmaida Sinaga (Warisan: Journal of History and Cultural Heritage, 2024)
This study explores the historical buildings in Medan, which serve as vital cultural heritage from the Dutch colonial era in North Sumatra. These well-preserved structures stand as monumental evidence of the past and are legally recognized as heritage sites. Over time, the area that once served as the administrative center has undergone significant transformations, evolving into a commercial hub. This shift has resulted in physical modifications, functional repurposing, and the emergence of new constructions that disrupt the architectural harmony of the colonial-era landscape. Employing a historical research method—encompassing heuristic analysis, source criticism, interpretation, and historiography—this study investigates the impact of colonialism on Medan’s urban development. The findings indicate that the visual identity of Lapangan Merdeka is predominantly defined by its physical elements, particularly the enduring presence of Dutch colonial buildings. The area’s architectural character is shaped by key design principles, including uniform building heights, structural alignment, roof typology, and spatial arrangements between buildings. This research underscores the growing threat posed by urban modernization to Medan’s historical integrity, emphasizing the urgent need for conservation strategies to preserve its colonial architectural heritage and cultural significance.